Strengthening of RC beams using prestressed fiber reinforced polymers - A review - Aslam, M.; Shafigh, P.; Jumaat, Mohd Zamin; Shah, S.N.R. (Elsevier, 2015)
The use of steel and fiber reinforced polymers (FRPs) for strengthening RC beams can significantly improve the flexural strength, fatigue life and the serviceability of the beams compared to un-strengthened beams. Prestressing materials enable the material to become more efficient since a greater portion of its tensile capacity is employed. Investigations have shown that prestressed FRPs are effective materials for strengthening deteriorated structures. This paper presents a comprehensive review on the flexural behavior of strengthened RC beams using prestressed FRPs. The review covers the near surface mounted (NSM), externally bonded reinforcement (EBR) and externally post-tensioned techniques (EPT) and the corresponding advantages and disadvantages are highlighted. Anchorage systems and the effect of pre-stressing levels on the ductility, deformability and bond behavior of prestressed FRPs are also addressed. Recommendations for the future research are also presented. (C) 2015 Elsevier Ltd. All rights reserved.